465 NICOTINE REGULATES PLACENTAL MYOFIBROBLAST DIFFERENTIATION. (1st January 2005) - Piroozi, A.; Bertolotto, C.; Ubal, V.; Moghimi, A.; Acuna, D.; Honrubia, D.; Wang, C.; Wachsmann-Hogiu, S.; Farkas, D.; Simmons, C. F.
Abstract : Background: Myofibroblasts are specialized mesenchymal cells that contribute to developmental fibrotic disorders, including placental fibrosis associated with intrauterine growth restriction. Although smoking is associated with abnormal placental vasculature and fibrosis, the effects of nicotine on the differentiation of placental myofibroblasts are poorly understood. Objective: We hypothesize that nicotine regulates placental myofibroblast differentiation, thus inducing abnormal placental vascular structure and regulation. Design/Methods: We developed a transgenic mouse line expressing EGFP driven by a smooth muscle actin enhancer-promoter region, in which myofibroblasts develop EGFP fluorescence. Primary fibroblasts were cultured, immortalized with an SV40 T antigen construct, and clonally expanded. Placental myofibroblasts were exposed to nicotine or nicotine plus hexamethonium bromide, a nicotinic ACh receptor antagonist, for up to 72 hours versus controls. Cultured cells were subjected to quantitative EGFP FACS analysis, confocal microscopy, immunohistochemistry with image analysis, Affymetrix microarray analysis, and RT-PCR to quantitate changes in gene and protein expression. Results: Nicotine induced placental myofibroblast contraction, an effect antagonized by hexamethonium and associated with increased cytoplasmic calcium concentration. Placental myofibroblasts express α3 nACh receptor subunits. Exposure to nicotine resulted in an acute increase in EGFP cytoplasmic and nuclear fluorescence, followed by reduction in total EGFP positive cells over 72 hours. Nicotine induced accumulation of VEGF a and c mRNA and progressive expression of proteins associated with myofibroblast differentiation. Conclusion: These results demonstrate that nicotine induces receptor mediated myofibroblast differentiation, contraction, and apoptosis. Myofibroblasts are major constituents of the labyrinthine zone of the murine placenta, and are strategically located to regulate placental angiogenesis, blood flow and extracellular matrix composition. Therefore, nicotine may directly and/or indirectly contribute to abnormal placental vasculature, placental fibrosis, and intrauterine growth restriction associated with smoking.